2003
DOI: 10.1097/00024720-200308000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stabilization of the Lumbar Spine and Its Effects on Adjacent Segments

Abstract: In recent years, nonfusion stabilization of the lumbar spine has gained more and more popularity. These nonfusion systems intend to maintain or restore the intersegmental motions to magnitudes of the intact spine and have no negative effects on the segments adjacent to the stabilized one. This study investigated the DYNESYS, a dynamic nonfusion system, which is designed to stabilize the bridged segments while maintaining the disc and the facet joints. To determine the magnitude of stabilization and the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
108
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(119 citation statements)
references
References 23 publications
8
108
1
2
Order By: Relevance
“…Beastall et al [7] studied 24 patients treated with Dynesys and at 9 months postoperatively found limited movement at the operative level and no signiWcant increase of mobility at the adjacent levels. Schmoelz et al [16] reported that Dynesys stabilization did not result in an increase in mobility of adjacent segments based on a study of cadavers. Schaeren et al [25] studied 19 patients with a minimum 4-year follow-up and found no measurable motion at the operative level, while new signs of degeneration were present in adjacent motion segments in 47% of the patient, a rate similar to that reported after lumbar fusion [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beastall et al [7] studied 24 patients treated with Dynesys and at 9 months postoperatively found limited movement at the operative level and no signiWcant increase of mobility at the adjacent levels. Schmoelz et al [16] reported that Dynesys stabilization did not result in an increase in mobility of adjacent segments based on a study of cadavers. Schaeren et al [25] studied 19 patients with a minimum 4-year follow-up and found no measurable motion at the operative level, while new signs of degeneration were present in adjacent motion segments in 47% of the patient, a rate similar to that reported after lumbar fusion [27].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the positive results reported with Dynesys, there is concern of the eVects of stabilization on adjacent segments, and a number of cadaveric, in vivo, and modeling studies have provided conXicting results [7,[16][17][18][19][20][21]. In addition, there have been few studies on the use of Dynesys for multisegment disease [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Extension movements causing compression of the device are restricted by the PCU spacer between the pedicle screws. However, biomechanical studies have shown, that the Dynesys device has a more motion restricting effect in flexion than in extension [7,8]. The newly developed Elaspine device (Spinelab AG, Winterthur, Switzerland) investigated in the present study is comprised of pedicle screws and a locking clip mechanism with a 360°form-fit connecting to an elastic PCU rod (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Its rationale, as dealt in the technique section, is to avoid facet joint overlapping by blocking them in a slightly flexed position to gain enough foraminal and spinal channel room that, even if not enough to be detected by imaging techniques, leads to clinically meaningful neural structures de-impingement anyway. If the articular facets motion range is limited on the sagittal plane, i.e., limiting hyperextension, the motion range on the coronal and axial planes, i.e., lateral and rotational movements respectively, are less limited to avoid restricting the motion degree of freedom of the segment instrumented, hence its mechanical behavior [36,37]. Moreover, right grounding on the above considerations and on the physical behavior, it is plausible to hypothesize that the device also decreases the load on the articular facets, thus decreasing the rate of degenerative changes, further delaying surgical indication.…”
Section: Discussionmentioning
confidence: 99%